Technological Frames, Organizational Capabilities, and IT Use: An Empirical Investigation of Electronic Procurement - Mishra, Abhay Nath; Agarwal, Ritu (Information Systems Research, 2010)
The process by which organizations incorporate technological innovations into existing routines and use them on a regular basis persists as a central concern in the literature. Although we now have a fairly robust understanding of the drivers of innovation adoption, the use of innovations is less understood. In this paper, we draw on two streams of literature, managerial and organizational sensemaking, and organizational capabilities that have hitherto been used independently, to investigate organizational use of information technology (IT)-based innovations. Building on and extending prior work, we posit that organizational capabilities serve as complements to managers' technological frames related to an innovation. We focus on the use of an important technological innovation—business-to-business (B2B) electronic markets for procurement. We examine interactions between three technological frames—benefits frame, threat frame, and adjustment frame, and two organizational capabilities—technological opportunism and technological sophistication, and their relationship with the use of B2B electronic markets in firms. We test our research model using survey data collected from 292 firms. Results largely support the proposed conceptualization and shed new light on the key factors associated with firms' use of B2B electronic markets. Theoretical and practical implications of the findings are discussed.